Analysis of serum and endometrial progesterone in determining endometrial receptivity. Issue 11 (12th August 2021) - Labarta, E; Sebastian-Leon, P; Devesa-Peiro, A; Celada, P; Vidal, C; Giles, J; Rodriguez-Varela, C; Bosch, E; Diaz-Gimeno, P
Abstract: STUDY QUESTION: Is there a relationship between serum and endometrial progesterone (P4) levels, including P4 and metabolites (oestrone, oestradiol and 17α-hydroxyprogesterone), and endometrial receptivity? SUMMARY ANSWER: Serum P4 levels were not correlated with endometrial P4, nor associated with endometrial receptivity as determined by the ERA ® test; however, endometrial P4 and 17α-hydroxyprogesterone levels were positively correlated and related to endometrial receptivity by ERA. WHAT IS KNOWN ALREADY: Acquisition of endometrial receptivity is governed by P4, which induces secretory transformation. A close relationship between serum P4 and pregnancy outcome is reported for hormone replacement therapy (HRT) cycles. However, the relationship between serum and uterine P4 levels has not been described, and it is unknown whether uterine receptivity depends more on serum or uterine P4 levels. STUDY DESIGN, SIZE, DURATION: A prospective cohort study was performed during March 2018–2019 in 85 IVF patients undergoing an evaluation-only HRT cycle with oestradiol valerate (6 mg/day) and micronised vaginal progesterone (400 mg/12 h). PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients were under 50 years of age, had undergone at least one failed IVF cycle, had no uterine pathology, and had adequate endometrial thickness (> 6.5 mm). The study was conducted at IVI Valencia and IVI Foundation. An endometrial biopsy and a blood sample were collected after 5 days of P4 vaginal treatment. Measures included serum P4 levels, ERA ® -based evaluation of endometrial receptivity, and endometrial P4 levels along with metabolites (oestrone, oestradiol and 17α-hydroxyprogesterone) measured by ultra-performance liquid chromatography–tandem mass spectrometry. MAIN RESULTS AND THE ROLE OF CHANCE: Seventy-nine women were included (mean age: 39.9 ± 4.6, BMI: 24.2 ± 3.9 kg/m 2, endometrial thickness: 8.2 ± 1.4 mm). The percentage of endometria indicated as receptive by ERA ® was 40.5%. When comparing receptive versus non-receptive groups, no differences were observed in baseline characteristics nor in steroid hormones levels in serum or endometrium. No association between serum P4 and endometrial steroid levels or ERA result was found ( P  <   0.05). When the population was stratified according to metabolite concentration levels, endometrial P4 and 17α-hydroxyprogesterone were significantly associated with endometrial receptivity ( P  <   0.05). A higher proportion of receptive endometria by ERA was observed when endometrial P4 levels were higher than 40.07 µg/ml (relative maximum) and a lower proportion of receptive endometria was associated with endometrial 17α-hydroxyprogesterone lower than 0.35 ng/ml (first quartile). A positive correlation R 2  = 0.67, P  <   0.001 was observed between endometrial P4 and 17α-hydroxyprogesterone levels. LIMITATIONS, REASONS FOR CAUTION: This study did not analyse pregnancy outcomes. Further, the findings can only be extrapolated to HRT cycles with micronised vaginal progesterone for luteal phase support. WIDER IMPLICATIONS OF THE FINDINGS: Our findings suggest that the combined benefits of different routes of progesterone administration for luteal phase support could be leveraged to ensure an adequate concentration of progesterone both in the uterus and in the bloodstream. Further studies will confirm whether this method can optimise both endometrial receptivity and live birth rate. Additionally, targeted treatment to increase P4 endometrial levels may normalise the timing of the window of implantation without needing to modify the progesterone administration day. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by the IVI-RMA Valencia (1706-VLC-051-EL) and Consellería d'Educació, Investigació, Cultura, i esport Generalitat Valenciana (Valencian Government, Spain, GV/2018//151). Almudena Devesa-Peiro (FPU/15/01398) and Cristina Rodriguez-Varela (FPU18/01657) were supported by the FPU program fellowship from the Ministry of Science, Innovation and Universities (Spanish Government). P.D.-G. is co-inventor on the ERA patent, with non-economic benefits. The other authors have no competing interests. TRIAL REGISTRATION NUMBER: NCT03456375.